Efficacy and Safety of GLP-1 Receptor Agonists in Patients With Type 2 Diabetes Mellitus and Non-Alcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Zhu, Yuan; Xu, Jiao; Zhang, Dong; Mu, Xingyu; Shi, Yi; Chen, Shangtao; Wu, Zengxiang; Li, Shuangqing (Frontiers in Endocrinology, 2021)
The prevalence of non-alcoholic fatty liver disease (NAFLD) in patients with type 2 diabetes mellitus (T2DM) is increasing and there is an urgent need for new treatment strategy to prevent progression of hepatic steatosis and fibrosis. We have performed a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the efficacy and safety of glucagon-like peptide-1 receptor agonists (GLP-1RAs) in the treatment of hepatic steatosis and fibrosis in patients with T2DM and NAFLD. The PubMed, Web of Science, Scopus, Embase and Cochrane Central Register of Controlled Trials databases were searched for articles that met the eligibility criteria to explore the efficacy and safety of GLP-1RAs in patients with T2DM and NAFLD. We assessed pooled data using a random/fixed-effects model according to the I2 and p-values. Eight trials that included a total of 468 participants were eligible for inclusion in the review. For primary outcomes, administration of GLP-1RAs significantly decreased the content of intrahepatic adipose (IHA)[p=0.007, weight mean difference (WMD) -3.01, 95% confidence interval (CI) -4.75, -1.28], subcutaneous adipose tissue (SAT) (p<0.00001,WMD -28.53,95%CI -68.09,-26.31), and visceral adipose tissue (VAT) (p<0.0001,WMD -29.05,95%CI -42.90,-15.9). For secondary outcomes, GLP-1RAs produced a significant decrease in levels of alanine aminotransferase(ALT）(p=0.02, WMD -3.82, 95%CI -7.04, -0.60), aspartate aminotransferase (AST) (p=0.03, WMD -2.4, 95%CI -4.55,-0.25, I2=49%), body weight (p<0.00001,WMD -3.48,95%CI -4.58,-2.37), body mass index (p<0.00001,WMD -1.07,95%CI -1.35,-0.78), circumference waist (p=0.0002,WMD -3.87, 95%CI -5.88, -1.86) fasting blood glucose (p=0.02, WMD -0.35, 95%CI -0.06, -0.05), HbA1c (p<0.00001,WMD -0.39,95%CI -0.56,-0.22), HoMA-IR(p=0.005, WMD-1.51, 95%CI-0.87,-0.16),total cholesterol (p=0.0008, WMD -0.31, 95%CI -0.48, 0.13)and triglycerides (p=0.0008,WMD -0.27, 95%CI -0.43,-0.11) in comparison with the control regimens. The main adverse events associated with GLP-1RAs included mild-to-moderate gastrointestinal discomfort and nonsense hypoglycemia that resolved within a few weeks.GLP-1RAs were an effective treatment that improved intrahepatic visceral and subcutaneous adipose tissue, inflammatory markers, the anthropometric profiles and some metabolic indices in patients with T2DM and NAFLD, GLP-1RAs could be considered for use in these if there are no contraindications. Further studies are needed to understand the direct and indirect effects of GLP-1RAs on NAFLD and the potential mechanism via which they prevent its progression.